Thermophysiology, haematology, reproductive hormones and antioxidative status of rabbit does fed graded levels of natural oils (Agriculture, Food, and Natural Resources Journal, 2025)
The experiment investigated the effect of black seed oil (BSO), olive oil (OO), and shea butter oil (SBO) on selected physiological parameters in rabbit does to improve their productivity. The study lasted for 8 weeks. Twenty-eight rabbit does were randomly allotted to 7 treatments comprising control (0 ml), 0.5 ml, and 1.0 ml for each of BSO, OO, and SBO within a 2x3+1 factorial laid in a completely randomized design. Respiratory rate (RR) and rectal temperature (RT) of the does were determined twice a week throughout the study. Haematology, selected hormones, antioxidant enzymes, and capacity were evaluated at the end of the experiment. Data was subjected to analysis of variance, and significant means were separated using Duncan's Multiple Range Test (α0.05) on RR. The interaction effect of the oils and their levels was significant on the RT of the does though only OO reduced RT as its level of inclusion increased. Oils and their levels had no effect on the blood profile of the does. The OO group had significantly higher (p0.05) among treatments. It was concluded that experimental oils did not impair the physiology, haematology and oxidative mechanism of studied animals. Hence, the oils could be utilized in improving rabbit doe production.
Keywords: Oestrogen; Oxidative mechanism; Physiology; Red blood cell; White blood cell